Four new polymorphisms in the human dystrophin gene from an Argentinian population - Baranzini, Sergio Enrique; Lenk, Uwe; Szijan, Irena; Speer, Astrid (Muscle & nerve, 1997)
Duchenne muscular dystrophy and its allelic disorder Becker muscular dystrophy are among the most common hereditary human pathologies (1:3500). Two thirds of the genomic alterations responsible for these diseases involve gross gene rearrangements such as deletions, and less frequently duplications. The remaining one third includes point mutations such as deletions, insertions, and substitutions. This study describes four nonpreviously reported polymorphisms in the dystrophin gene by using the polymerase chain reaction/single‐strand conformation polymorphism technique and subsequent nonisotopic silver staining. © 1997 John Wiley & Sons, Inc. Muscle Nerve 20: 1451–1453, 1997